Analisis Gender dalam Pendidikan: Tantangan dan Peluang Di Era Digital (Jurnal Sosial Humaniora dan Pendidikan, 2025)
This study aims to explore the challenges and opportunities faced by female students in education in the digital era, focusing on gender equality issues. The background of this research is based on the increasing awareness of the importance of gender equality in education, yet there are still barriers faced by female students. The method used is a qualitative approach with case studies, involving students from various educational levels as well as female teachers and mentors. The results show that better access to digital technology can help female students overcome gender stereotypes and enhance their skills. Additionally, connections with female mentors play a crucial role in building self-confidence and providing necessary support. This research concludes that the establishment of digital communities and educational programs that support technology access are essential for increasing female student participation. Recommendations include the need for practical actions in creating support programs, the development of the "Gender Digital Literacy" theory, and further research to explore the long-term impacts of these initiatives. These findings are expected to contribute to understanding the dynamics of gender equality in education and encourage the implementation of more effective strategies